Analisis Isi Berita Demonstrasi Bersih 4.0 pada Fajar, Tribun Timur, Sindo - Ramli, Ruslan (JPP (Jurnal Politik Profetik), 2015)
This research was carried out using descriptive content analysis method with the purpose of revealing the tendency of some local newspapers such as Fajar, Tribun TImur, and Sindo in covering the demonstration of Bersih (Clean) 4.0 in Kuala Lumpur which was published on August 29, 2015 to September 2, 2015. The results of this research show the similarities and differences of news coverage of Fajar, Tribun Timur, and Sindo in reporting the demonstration. In reporting the news, Fajar, Tribun Timur, and Sindo have tendency to lean to sup[ort the agenda of the demonstrators instead of supporting the Malaysian government in its program of Bersih 4.0. All three also apply the theory of agenda setting and focusing more on war journalism, than peace journalism.